SERVICE CENTERS: ANALYSIS OFCHALLENGES AT DIFFERENT DEVELOPMENTAL STAGES - Almeida, Marcelo Paixão; Domingues, Carlos Roberto (Revista Gestão da Produção Operações e Sistemas, 2020)
Purpose – To link the different levels of maturity of Service Centers (SCs) in multinational companies to the challenges faced by this organizational arrangement. Design/methodology/approach – Using a qualitative approach, we conducted a multiple case study with data collection, via semi-structured interviews, with managers of three multinational companies, based in SCs in southern and southeastern Brazil. The interviews were recorded and transcribed, and a content analysis was made based on four pre-defined categories using a theoretical framework. Findings – Results show that challenges arise depending on the Center’s level of development and are related to organizational structure; cost reduction; customer relationship management; and processes. Some challenges have always recurred at SCs, others are not relevant initially, and then become more important, while others decrease in complexity over time. Originality/value – As a theoretical contribution, in addition to proposing a three-stage analysis, this study demonstrates the importance of examining each with its specific challenges. The understanding that a SC develops based on tensions and solutions demonstrates the dynamics and complexity of this phenomenon. The study also encourages and guides managers in organizations, who are planning a SC or who already have one set up, to align their resources and work with the measures needed to deal with the challenges of each stage and maximize the use of resources for better results at the SC. Keywords - Service Center. Service Center Stages. Organizational management